EFFECT OF TIME HORIZON ON WIND SPEED PREDICTION WITH ANN - Pusat, S.; Akkoyunlu, M. T. (YILDIZ TECHNICAL UNIV, 2018)
Proper utilization of renewable energy sources in electricity production is inevitable due to the environmental concerns and global warming fight. Therefore, predictability of renewable electricity is a very significant issue for a long time. Main aim of this study, different from the literature, is to investigate the change of wind speed prediction errors for different time horizons. Different prediction time horizons (10, 30, 60, 90 and 120 minutes) were used, and the results were compared through the error measures and the regression values. The mean squared errors and the regression values vary between 0.819 and 5.570, and between 77.8% and 97.1%, respectively. The prediction error changes almost logarithmically, and the rate of change decreases with the increasing time horizon. A new analysis approach was proposed to see the change of the prediction error with time horizon. The equation, y = 1.5413ln(x) - 2.7428, representing the change of the mean squared error with time horizon was obtained.
Keywords: Wind Energy; Wind Speed Prediction; Artificial Neural Network; Time Horizon; ARTIFICIAL NEURAL-NETWORKS; POWER; SERIES; FORECAST; STATIONS; SYSTEMS; MODELS; Thermodynamics